Studies on nickel segregation process using alkali chloride - Balacuit, Rosalinda C.
A combined process of segregation - ammonia leaching to examine the effects of alkali chlorides on nickel recovery was developed. Of the three alkali chlorides studied (potassium chloride, sodium chloride and lithium chloride), potassium chloride is the most efficient followed by sodium chloride. The effect of three process variables (roasting temperature, roasting time and relative amounts of carbon and alkali chloride) on nickel recovery were also investigated. Nickel recovery is high at high levels of potassium chloride. It is optimum at roasting temperature of 850°C, roasting time of 1.0 hr and 3.5 % carbon addition. On the other hand, it is low at variable levels below and beyond such three conditions. This is because increased reducing condition in the segregation bed at high levels of the process variables promotes in-situ reduction which impairs segregation reaction. Although nickel is metallized durign the in-situ reduction at high levels of the process variables, a fraction of the metallized nickel is redissolved in the refractory spinel and in the recrystallization of hematite into lower iron oxides. Also, at high levels of these process variables nickel is trapped during the transformation of serpentine to the forsterite, resulting in low nickel recovery.